'If You Find One Politician and Convince Him About the Importance of Dance for the Society, You Have Done a Lot': Interview with Ingo Diehl, director of Tanzplan Educational Programme. Issue 159 (1st December 2013) - Jež Furlan, Jedrt
Dancer, choreographer and dance pedagogue Ingo Diehl gives an interview about the network project Tanzplan Deutschland, which, between 2005 and 2010, connected dance schools, universities, academies, artists and local communities. The German Federal Cultural Foundation has approved funds of EUR 12.5 million for the project for a period of five years: the result was the participation of 70 internationally renowned artists, 70 universities, 180 participants. How to address politicians, the broader public and the local community? Ingo Diehl talks about networking, solidarity and the common good. And about how contemporary dance can contribute to all this.